2001
DOI: 10.1088/1126-6708/2001/01/004
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on twisted theories with matter

Abstract: We investigate some aspects of N = 2 twisted theories with matter hypermultiplets in the fundamental representation of the gauge group. A consistent formulation of these theories on a general four-manifold requires turning on a particular magnetic flux, which we write down explicitly in the case of SU (2ℓ). We obtain the blowup formula and show that the blowup function is given by a hyperelliptic σ-function with singular characteristic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…8) Recently it is shown that the prepotential satisfies further nontrivial equations 24) obtained from the Whitham hierarchy. Instanton correction to the prepotential has been calculated in this framework 25) for some gauge theories. It would be interesting to study the relation between the WDVV equation approach and this formulation.…”
Section: K Itomentioning
confidence: 99%
“…8) Recently it is shown that the prepotential satisfies further nontrivial equations 24) obtained from the Whitham hierarchy. Instanton correction to the prepotential has been calculated in this framework 25) for some gauge theories. It would be interesting to study the relation between the WDVV equation approach and this formulation.…”
Section: K Itomentioning
confidence: 99%